Gender time: Quality money for quality work - Baltenweck, Isabelle (International Livestock Research Institute, 2016)
The gender initiative started when the team started to focus on “quality money” for “quality work”. An open call for proposals to integrate gender in research led to excellent feedback: at least 20 positive proposals. Decisions on which projects to fund were taken based on certain criteria. The program also initiated a coaching track for projects to be supported in their efforts to integrate gender. Gender has helped the research centres to come together around one topic: technical and social scientists coming together. For the second phase of the program, the CGIAR research “flagships” (focus areas) and technical teams will integrate gender in their work from the beginning. The approaches will evolve, but collaboration between centers and teams will remain. Interview with Isabelle Baltenweck (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684